AN ANALYSIS OF STUDENTS’ STRATEGIES IN SPEAKING ENGLISH IN THEIR CLASSROOM INTERACTION - Marliani, Astri; Muljanto, Setia; Suminar, Anne Ratna (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This study investigated strategies in learning speaking was used by the students. Besides that, the purpose of this study is to find out the students’ strategies in learning speaking English in their classroom interaction. To achieve the purpose, the study used qualitative as research method and participant observation design. The objects of this study were 10 students of 1st grade in one college in Garut. The primary data collections of the current study were observation and questionnaire. This study used observation check list form to find out the students’ speaking classroom activities Based on the research findings in the observation, showed that the students were story telling about narrative text in front of class individually like actress/actor. After performing, they got the score from their showed about used grammar, pronunciation, character, and their voices (loudly, slowly and clearly). Meanwhile, in the questionnaire, showed that the students used some learning strategies to improve their speaking classroom interaction, the strategies are: 1) Watching English movie with the subtitle. 2) Making conversation in speaking English in daily activities. 3) Finding the new vocabulary. 4) Listening to the music or song. 5) Listening to their friend when speaking English in front of class. Therefore, the students have to practice used their strategies in learning speaking classroom interaction to be more actively and confidence